The Discursive Construction of Certainty and Uncertainty in the Scientific Texts of Forensic Psychiatry - Scardigno, Rosa; Grattagliano, Ignazio; Manuti, Amelia; Mininni, Giuseppe (East European Journal of Psycholinguistics, 2020)
A common ground between mental health and judicial-legal domains concerns concepts like “care”, “control” and “possibility to foresee” human behaviour, with particular reference to the “social dangerousness”. The connections between these sense-making practices can be traced by discursive modulation of “certainty/uncertainty”. This study aimed to highlight the discursive peculiarities of a specific socio-cultural context and genre, namely scientific papers. The corpus of data consisted in a selection of 30 papers published by the BJP (from 1975 to 2015), on subjects concerning forensic psychiatry, subjected to Content Analysis and Critical Discourse Analysis. Results showed that the papers adopted two main socio-epistemic rhetorics. On one side, the enunciators proceeded in an “assertive” and rigorous manner through a social-epistemic rhetoric of “reassurance”; on the other side, they gave voice to rhetoric of the “limit”, lacking any cognitive “closure”.